PENGEMBANGAN HANDOUT YANG DIAWALI PETA KONSEP PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN UNTUK SMA - Yurnita, Elni; Risdawati, M.Si., Renny; Susanti, Diana (STKIP PGRI Sumbar, 2014)
ABSTRACT The meaning media as mediator or connector between receiver of message or information. Media also as form for deliver the infotmation. Based on the observation and interview, the teacher in SMAN 1 V Koto Kampung Dalam in the school, do not use the handout that begin with concept map. The students only using a book colour, so do not appropriate with the real object and do not use the concept map. Concept map is a note production technique with using words in one point or concept of a mind that arranged in a connected with one pattern. The purpose of this research is resulted the handout that begin with concept map to structure and function of plants network valid and practice.The research develop by using model 4-D, consist of four step: define, design, develop and disseminate, but in this research only in develop step because of limited cost. Handout research that begin with concept map in structure and function of plants network for SMA which have been developed to be expressed in valid and practice category with the average in the validity by the lecturer and teacher the result 82,71% with valid category. Test practicalities of teachers the average is 85.56% with practice category. Test practicalities by the student, the average is 83,53% with practice category. Based on the result which obtained that handout that begin with concept map already develop is valid and practice for teacher and students.